Pengaruh self efficacy terhadap hasil belajar mahasiswa berprestasi (mawapres) STKIP PGRI Bangkalan - Atya Rizkiana (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
The purpose of this research is to know how big influence of self efficacy variable consist of; Level, strength, generality to the learning outcomes of Mawapres (outstanding students) in STKIP PGRI Bangkalan. Where, students are taken are students who follow the mawapres in STKIP PGRI Bangkalan as many as 22 people. The analysis technique used multiple linear regression analysis. The hypothesis of this study is Self Efficacy consisting of variable level, strength and generality influence on student learning outcomes. Based on hypothesis testing is acceptable. The findings of this study indicate that self efficacy variables consisting of: Level, Strength, and Generality have a significant effect on the result of learning mawapres STKIP PGRI Bangkalan. And obtained the value (R²) = 0.643 means the variable Level, Strength, and Generality gives the effect of 64.3% of academic achievement, while the remaining 35.7% influenced by other factors outside the variables studied.